2021
DOI: 10.1007/s15010-020-01572-8
|View full text |Cite
|
Sign up to set email alerts
|

Left and right ventricular dysfunction in patients with COVID-19-associated myocardial injury

Abstract: Purpose SARS-COV-2 infection can develop into a multi-organ disease. Although pathophysiological mechanisms of COVID-19-associated myocardial injury have been studied throughout the pandemic course in 2019, its morphological characterisation is still unclear. With this study, we aimed to characterise echocardiographic patterns of ventricular function in patients with COVID-19-associated myocardial injury. Methods We prospectively assessed 32 patients hospi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
2
7

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(61 citation statements)
references
References 21 publications
2
45
2
7
Order By: Relevance
“…In patients with COVID-19, E/e′ which is reflective of LV filling pressures was not found to be elevated in patients with elevated HsT or other cardiac biomarkers. 44,46,57 Further, E/e′ ratio was not significantly altered in the severe forms of COVID-19 compared with mild form or between survivors and non survivors. 44,53,55,57,70,71 Of note, in a study of COVID-19 patients that included 90% of patients on mechanical ventilation and 50% in prone position showed that E/e′ ratio was significantly higher in non-survivors, and it was a predictor of mortality on univariate but not on multivariate analysis.…”
Section: E/e′ Ratiomentioning
confidence: 78%
See 3 more Smart Citations
“…In patients with COVID-19, E/e′ which is reflective of LV filling pressures was not found to be elevated in patients with elevated HsT or other cardiac biomarkers. 44,46,57 Further, E/e′ ratio was not significantly altered in the severe forms of COVID-19 compared with mild form or between survivors and non survivors. 44,53,55,57,70,71 Of note, in a study of COVID-19 patients that included 90% of patients on mechanical ventilation and 50% in prone position showed that E/e′ ratio was significantly higher in non-survivors, and it was a predictor of mortality on univariate but not on multivariate analysis.…”
Section: E/e′ Ratiomentioning
confidence: 78%
“…44,46,57 Further, E/e′ ratio was not significantly altered in the severe forms of COVID-19 compared with mild form or between survivors and non survivors. 44,53,55,57,70,71 Of note, in a study of COVID-19 patients that included 90% of patients on mechanical ventilation and 50% in prone position showed that E/e′ ratio was significantly higher in non-survivors, and it was a predictor of mortality on univariate but not on multivariate analysis. 52 However, two reports demonstrated that E/e′ ratio may be significantly higher in critically ill patients compared with healthy volunteers and milder forms of the disease.…”
Section: E/e′ Ratiomentioning
confidence: 78%
See 2 more Smart Citations
“…Other studies suggest that HF incidence may be even higher. Bieber et al observed that left ventricular dysfunction (both systolic and/or diastolic) and systolic right ventricular dysfunction occurred in 56% of their total cohort (116 pts) and more frequently in patients with increased troponin (88.8% vs. 14.3%, p < 0.001) [71]. Moreover, this complication occurs regardless of a prior history of CD [72], suggesting a direct role of SARS-CoV-2 infection in its pathogenesis.…”
Section: Heart Failurementioning
confidence: 97%